Journaling as a Medium for Narrative Discourse Development: A Qualitative Analysis in an Indonesian EFL Setting" - Susanto, Dias Andris (Global Synthesis in Education Journal, 2025)
This qualitative study at Mamina English Course in Batam explored how journaling helps first-grade junior high students improve their English narrative writing. Many students learning English in Indonesia often struggle with vocabulary, grammar, and expressing ideas freely. This research aimed to find more engaging teaching methods. Journaling seemed promising because it's a relaxed way to write, reducing anxiety and encouraging practice. Ten students journaled regularly for a month. Data from surveys and writing tests, informed by key language acquisition theories and teaching approaches, showed positive results. Students reported increased motivation, engagement, creativity, self-expression, and writing confidence. To understand this better, our study gathered detailed information from ten students over one month. We used surveys to hear directly about their experiences and also looked at their writing tests. The ideas behind our study come from important theories about how people learn a second language. For example, Stephen Krashen's Affective Filter Hypothesis suggests that feeling relaxed helps learning, and journaling certainly offers that. Merrill Swain's Output Hypothesis highlights the importance of language production, and journaling offers numerous opportunities for this practice. We also explored the role of motivation in student learning and how Discourse Analysis can reveal students' language usage. On the instructional side, we examined Process Writing, which emphasizes the stages of writing, and Constructivism, which posits that learners actively construct their own understanding. Although the findings do not establish a direct cause-and-effect relationship, they indicate that journaling creates a supportive atmosphere for self-expression and language experimentation. The study underscores the potential of journaling to empower young English learners and advocates for its inclusion in educational curricula, along with suggestions for further research.